Researching Accounting Information System (Global Business Management Review (GBMR), 2022)
Revolution of information technology (IT) has changed many aspects of accounting practices, which have resulted in greater demand for IT-literate accountants. From the research perspective, changes to the accounting practices have provided new and exciting research opportunities for accounting information system (AIS) researchers. However, as a relatively young discipline that has just begun to mature, AIS research thus far has provided very limited contribution to the accounting or information system research and practice. Therefore, this paper aims to address issues and the direction of AIS research. More specifically, it discusses the definition, scope, and category of AIS research. This paper ends with several suggestions for the AIS researchers. Among others, AIS researchers need to view AIS in a broader perspective where the impact of technology on all areas of accounting, auditing, and taxation should be considered within the realm of AIS interest. Secondly, AIS researchers have to specialise in at least one other accounting area such as financial reporting, managerial accounting, audit, or taxation, in addition to the AIS domain, to produce high-quality research results. It is hoped that discussions and suggestions brought forward by this paper would initiate and encourage debate among AIS researchers in order to produce high-quality AIS research that can have notable impact on the accounting profession and business practice.